A quantitative study of early intervention and the impact on social emotional learning - Lowe, Christopher Daniel (My University, 2024)
The purpose of this study was to determine how an Early Learning Program supported social emotional learning and skill development for students preparing to enter kindergarten. Further, the study examined if teacher-led activities focused on early learning skills aligned to the Kansas Early Learning standards resulted in increased evidence of social emotional skills. The proxy used to determine this relationship was the existence of behavior referrals during the kindergarten school year in a mid-western state school district. Thus, the study’s design aimed to determine if an early intervention program equipped pre-kindergarteners with the social and emotional skills necessary to be successful in kindergarten as measured by behavior referrals. Descriptive statistics and logistical and multiple regression models with control were utilized to determine relationships between participation in the early learning program. Relationships studied included participation in the program and referrals measured at quarterly intervals during the kindergarten year. Relationships were also studied when controlling for race, gender, students receiving free and or reduced meals, students with disabilities, and English Language Learners. This study correlated the Kansas Early Learning Standards to each of the behavior codes utilized by The School District. This correlation allowed the researcher to determine if a specific social emotional skill showed a stronger relationship to participating students compared to peers who did not participate in the program. The three specific skills taught were kindness, feelings, safety and learning. The results of this study found participation in the three-week Early Learning Program did have a statistically significant relationship to social emotional learning compared to peers who did not participate in the program. When reviewing the data at quarterly intervals during the kindergarten year, results showed a significant relationship for the second quarter and third quarter and no significant relationship for the first quarter and fourth quarter. The study also found a relationship for Hispanic, Asian, and White students in addition to English Language Learners. The information and relationships observed can be used to support future programing, areas of focus for additional research, and expansion of early intervention funding.
Keywords: Social emotional learning; Social emotional skills; Behavior referrals; Early learning program